The encyclopedia of volcanoes (second edition) - Scarpati, Claudio (Geologos, 2019)
Book review: The encyclopedia of volcanoes (second edition), by Haraldur Sigurdsson, Bruce Hought-on, Steve McNutt, Hazel Rymer and John Stix (Eds.), 2015. Academic Press, USA. 1,456 pages. Hardback: price $133,00, ISBN 978-0123859389.